A Comparative Analysis of Agency Monitoring Cost and Financial Performance of Financial and Non-Financial Companies in Nigeria - Awuhe, Patrick Orbanga; Orshi, Teryima Samuel (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Corporate governance is vital for transparency, accountability, and efficiency in organizational management. A key aspect of corporate governance is agency monitoring, which entails costs incurred to oversee managerial actions and align them with shareholders' interests. However, the impact of agency monitoring expenses on financial performance varies across sectors. Financial institutions, subject to strict regulatory oversight, require intensive monitoring, whereas non-financial firms may experience less scrutiny. Understanding these differences is crucial for policymakers, investors, and corporate managers aiming to enhance financial performance while maintaining strong governance. This study employs a correlational research design to examine the relationship between agency monitoring cost and financial performance in listed financial and non-financial firms in Nigeria. Based on market capitalization, the analysis covers 20 firms—10 financial and 10 non-financial—selected from 157 companies listed on the Nigerian Exchange Group (NGX) between 2011 and 2020. Data were sourced from the firms' annual reports and analyzed using panel regression estimates. Findings indicate that agency monitoring costs significantly enhance financial performance in financial firms, while their impact on non-financial firms is minimal. These results align with agency theory, which stresses the necessity of stringent oversight to mitigate managerial opportunism. The study underscores the sectorial differences in agency monitoring effectiveness and recommends that financial institutions prioritize monitoring expenses to improve governance and performance by strategically investing in efficient oversight mechanisms that align managerial actions with shareholder interests. These insights contribute to corporate governance literature and provide practical guidance for firms seeking to balance monitoring costs with financial efficiency.